PENGARUH PEMAKAIAN KULIT BUAH NAGA MERAH TERHADAP KUALITAS KUE KU - Sepryadi, Tri; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2015)
This study aimed to analyze the effect of the use of the red dragon fruitrind as much as 0%, 35%, 50% and 65% of the quality of shape, color, fragrance,texture and flavor on kue ku. Type of research is pure experiment (trueexperiment) with completely randomized design method. The data used is primarydata obtained directly from the 30 panelists who gives an answer of organoleptictest format containing the test level and hedonic test of the quality of kue ku. Thedata has been obtained and tabulated in tables and do Variant Analysis(ANOVA), if significantly different followed by Duncan test. Based on dataanalysis of this study showed that the quality of the test levels, namely the shape,color, flavor (milk), aroma (not scented rind dragon fruit) and texture significanteffect whereas no effect taste. In the hedonic test, namely the shape, color andtexture significant effect while the flavor (milk), falvor (not scented red dragonfruit rind) and a sense of no effect. It can be concluded the use of the red dragonfruit peel percentage of 65% is best used on the quality of color, and texture onkue ku.Keywords: red dragon rind, kue ku, kue ku quality